Depression in pregnancy. Prevalence and associated factors - de Jesus Silva, Monica Maria; Peres Rocha Carvalho Leite, Eliana; Alves Nogueira, Denismar; Clapis, Maria José (Investigación y Educación en Enfermería, 2016)
Objective. To evaluate the occurrence of depression during pregnancy and its associated factors. Methods. Epidemiological, quantitative, descriptive and cross-sectional study, conducted from January to May 2013 with 209 pregnant women in the city of Alfenas, State of South Minas Gerais, Brazil. The Hospital Anxiety and Depression Scale (HASD) of Zigmond y Snaith and a form for characterization of participants were used for data collection. Results. Depression was present in 14.8% of the pregnant women and was more frequent during the second trimester of pregnancy. Depression during pregnancy was significantly associated with number of births, number of children, ranking as the number of pregnancies, family support, amount of cigarettes smoked per day, consumption of alcohol, use of daily medications, history of mental disorder, presence of striking events in the last 12 months and history of domestic violence. Conclusion. The evaluation of depression showed that this disorder is common during pregnancy, and the risk is higher among primigravidae women, women who use alcohol, use daily medications, have history of mental disorder, have experienced a striking event in the last 12 months and who have suffered domestic violence. Knowledge of the factors associated with occurrence of depression allows early adoption of interventions to monitor the mental health of women throughout pregnancy, preventing this and other disorders. How to cite this article: Silva MMJ, Leite EPRC, Nogueira DA, Clapis MJ. Depression in pregnancy. Prevalence and associated factors. Invest. Educ. Enferm. 2016; 34(2):